Antenatal care services in Benin and Tanzania 2021/2022: an equity analysis study - Julie Gutman; Walter Ochieng; Anna Munsey; Alen Kinyina; Melkior Assenga; Faustin Onikpo; Alexandre Binazon; Marie Adeyemi; Manzidatou Alao; Sijenunu Aron; Samwel Nhiga; Julie Niemczura; et al. (BMJ Publishing Group, 2024)
Introduction Antenatal care (ANC) interventions improve maternal and neonatal outcomes. However, access to ANC may be inequitable due to sociocultural, monetary and time factors. Examining drivers of ANC disparities may identify those amenable to policy change.Methods We conducted an ANC services equity analysis in selected public facilities in Geita, Tanzania, where most services are free to the end-user, and Atlantique, Benin, where every visit incurs user fees. Data on total ANC contacts, quality of care (QoC) indicators and wait times were collected from representative household surveys in the catchment of 40 clinics per country and were analysed by education and wealth. We used indices of inequality, concentration indices and Oaxaca-Blinder decompositions to determine the distribution, direction and magnitude of inequalities and their contributing factors. We assessed out-of-pocket expenses and the benefit incidence of government funding.Results ANC clients in both countries received less than the recommended minimum ANC contacts: 3.41 (95% CI 3.36 to 3.41) in Atlantique and 3.33 (95% CI 3.27 to 3.39) in Geita. Wealthier individuals had more ANC contacts than poorer ones at every education level in both countries; the wealthiest and most educated had two visits more than the poorest, least educated. In Atlantique, ANC attendees receive similar QoC regardless of socioeconomic status. In Geita, there are wide disparities in QoC received by education or wealth. In Atlantique, out-of-pocket expenses for the lowest wealth quintile are 2.7% of annual income compared with 0.8% for the highest, with user fees being the primary expense. In Geita, the values are 3.1% and 0.5%, respectively; transportation is the main expense.Conclusions Inequalities in total ANC visits favouring wealthier, more educated individuals were apparent in both countries. In Atlantique, reduction of user-fees could improve ANC access. In Geita, training and equipping healthcare staff could improve QoC. Community health services could mitigate access barriers.